The Rate of Neoadjuvant Chemotherapy Use in Muscle Invasive Bladder Cancer and The Approach of Urologists in Turkey - Üçer, Oktay; Albaz, Ali Can; Atag, Elif; Karaoglu, Aziz; Muezzinoglu, Talha (Urology Journal, 2016)
Purpose: To investigate the proportion of neoadjuvant chemotherapy (NAC) use in patients with muscle invasive bladder cancer before radical cystectomy and the approach of urologists to this subject. Materials and Methods: We invited 242 urologists during the 12th International Urooncology Congress in Turkey to answer a self-administered questionnaire. The questionnaire included questions related to radical cystectomy, lymph node dissection and neoadjuvant chemotherapy that had been performed in patients with muscle invasive bladder cancer by the urologist. Results: The median number of radical cystectomy operations was 20 per year. 122 (50.5 %) of 242 urologists had used neoadjuvant chemotherapy for the treatment of muscle invasive bladder cancer before radical cystectomy. The mean rate of neoadjuvant chemotherapy use by these urologists (n=122) was 28.46 %. The most common reasons for not using neoadjuvant chemotherapy by urologists in Turkey were as follows: (i) neoadjuvant chemotherapy might lead to a decrease in the cure rate of radical cystectomy due to delayed surgery (ii) complication rate of radical cystectomy might be elevated and the surgery might be complicated by NAC use. Conclusion: Although the European Association of Urology (EAU) guidelines panel on muscle invasive bladder cancer recommends using NAC in T2-T4a bladder, the rate of neoadjuvant chemotherapy use was still found to be low in our country because urologists have concerns about adverse effects NAC on radical cystectomy.